Dynamic Distribution of Gut Microbiota in Goats at Different Ages and Health States - Wang, Yujian; Zhang, Hao; Zhu, Lin; Xu, Yulin; Liu, Na; Sun, Xiaomei; Hu, Liping; Huang, He; Wei, Kai; Zhu, Ruiliang (Frontiers in Microbiology, 2018)
Abstract: The importance of the gut microbiota (GM) of animals is widely acknowledged because of its pivotal roles in metabolism, immunity, and health maintenance. The level of health can be reflected by the dynamic distribution of GM. In this study, we compared the microbial populations from feces in healthy and diarrheic lambs by using high-throughput sequencing technology to examine the dynamic shift of microbiota in lambs and investigated differences from adult healthy goats. Results showed a significant difference between diarrheic and healthy lambs and diarrheic lambs and healthy goats. Moreover, healthy lambs and goats not only displayed higher species richness but also exhibited higher bacterial diversity than diarrheic lambs based on the results of the operational taxonomic unit analysis, alpha diversity, and beta diversity. Firmicutes and Bacteroidetes were the most dominant phyla in all samples. At the genus level, the differences in diversity and abundance between diarrheic lambs and the other two groups were gradually observed. In the diarrheic lamb intestine, Bacteroides remained the dominant species, and the proportion of Clostridium_sensu_stricto_1 and Paeniclostridium increased, whereas Rikenellaceae_RC9_gut_group, Ruminococcaceae_UCG-005, and Christensenellaceae_R-7_group were significantly reduced. In addition, the predicted functional abundance of GM in diarrheic lambs was high, which showed a strong correlation with lamb diarrhea. This study is the first to investigate the distribution of intestinal flora in Boer goats with different ages and health states. Furthermore, this study will provide a theoretical basis for the establishment of a prevention and treatment system for goat diarrhea.